An In-Vitro Study on the Effect of Haemolysis in the Rbc’s Treated with Polyvinyl Alcohol (Pvoh) - Jiteesha V., Chavan; Vyas, Dhara; Tarun, Ugale; Aditi, Dhotre; Kanisha, Keer (Journal of Neonatal Surgery, 2025)
Microplastics have created a havoc in ecosystem.With the complexity that is included in making plastic products, the degradability of the said goes for a toss.In the context of plastics being found in water table to presence in the placenta has baffled not just the scientific community but also common man.Humans went ahead and searched for new options the water soluble plastics.These water soluble plastics came in with a big problem.Before they could degrade completely they entered the ecosystem.Dearth of data available on water soluble plastics in making it a new mystery.The impacts of these newly invented product on the environment,organisms is still unknown.In recent times,the idea of using polyvinyl alcohol has become very adamant with various invention using it as a drug delivery system,wound healing patches etc.There are no noted side effects yet if consumed orally but very less data available if entered into blood stream. The target of this study was to evaluate the haemolysis of RBCs treated by PVOH in vitro. Study has two main stages including sampling, preparation of PVOH suspension and haemolysis test. When 1 drop of RBC suspensions were treated for 60 min at room temperature with 0.1% to 1.0% PV (OH), they exhibited a significant level of haemolysis.